1985
DOI: 10.1111/j.1432-1033.1985.tb09279.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper ions as inhibitors of protein C of soluble methane monooxygenase of Methylococcus capsulatus (Bath)

Abstract: Copper(I), copper(I1) and silver ions have been shown to be potent inhibitors of purified soluble methane monooxygenase (MMO) of Methylococcus cupsulatus (Bath). A weaker inhibition has been observed with zinc and cadmium ions. Proteins A and B of soluble MMO are unaffected by copper but protein C is rapidly and irreversibly inhibited. The site of copper inhibition has been shown to be primarily at the iron-sulphur centre of protein C with a secondary effect at the FAD centre when the copper(1I):protein C rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 37 publications
1
61
0
Order By: Relevance
“…The observed inhibition pattern for A M 0 of Mycobacterium E3 is very similar to the inhibition patterns reported for the soluble methane monooxygenases of Methylococcus capsulatus (Bath) and Methylosinus trichosporiurn OB3b (Scott et al, 198 1 revealed the presence of an unusual non-haem iron centre (Green & Dalton, 1988). The iron in component A could be removed by dialysis against 8-hydroxyquinoline, resulting in an inactive protein.…”
Section: Inhibitors Of a M 0 Activitysupporting
confidence: 67%
“…The observed inhibition pattern for A M 0 of Mycobacterium E3 is very similar to the inhibition patterns reported for the soluble methane monooxygenases of Methylococcus capsulatus (Bath) and Methylosinus trichosporiurn OB3b (Scott et al, 198 1 revealed the presence of an unusual non-haem iron centre (Green & Dalton, 1988). The iron in component A could be removed by dialysis against 8-hydroxyquinoline, resulting in an inactive protein.…”
Section: Inhibitors Of a M 0 Activitysupporting
confidence: 67%
“…Thus, it seems to resemble the small protein B of the multicomponent soluble methane monooxygenase from methanotrophic bacteria. In the case of Methylococcus capsulatus (Bath) this 16-kDa protein is devoid of prosthetic groups and converts methane monooxygenase from an oxidase to an oxygenase (Green and Dalton, 1985;Lipscomb, 1994). However, no sequence similarity was found between protein B and the small subunits of the two-component monooxygenases (Pilkington et al, 1990;Cardy et al, 1991 ;Prieto and Garcia, 1994;Takizawa et al, 1995;this study).…”
Section: Spristinae: H T -A M -A -A a E F C V -S I L G E D (69-85)mentioning
confidence: 99%
“…A-naphthylamine in 30% (by vol.) acecycles [7]. After the fourth cycle the iron content was reduced tic acid.…”
Section: Growth Of Nocardia Corallina B-276 and Preparation Ofmentioning
confidence: 99%
“…A DEAE-cellubelieve particular residues are able to account for the difference lose (Whatman) FPLC column (250 mmϫ56 mm, 120 ml) in stereoselectivity observed between AMO [6] and soluble equilibrated with buffer B was used for initial seperation of the MMO [7].…”
Section: Fig 1 Comparison Of the Deduced Amino-acid Sequences Of Thmentioning
confidence: 99%
See 1 more Smart Citation